1973
DOI: 10.1104/pp.51.3.549
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gibberellic Acid and Actinomycin D on the Formation and Distribution of Rough Endoplasmic Reticulum in Barley Aleurone Cells

Abstract: and secretion by 63%. These cells were characterized cytologically by large areas of disarrayed segments of fragmented rough endoplasmic reticulum, corresponding to a high intracellular level of a-amylase. In addition, small lipid bodies common to the segmented regions of rough endoplasmic reticulum were surrounded by fine fibrous material, short segments of rough endoplasmic reticulum, and free ribosomes, suggesting that actinomycin D had interfered with development and organization of rough endoplasmic retic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1974
1974
1990
1990

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…We found no evidence for the disappearance of ER following heat stress. When ER was estimated from the (12) has been reported in barley aleurone following treatment with GA3 (10,20,21,26). …”
Section: Discussionmentioning
confidence: 99%
“…We found no evidence for the disappearance of ER following heat stress. When ER was estimated from the (12) has been reported in barley aleurone following treatment with GA3 (10,20,21,26). …”
Section: Discussionmentioning
confidence: 99%
“…The embryo secretes gibberellin (13,34,44), and it has been shown that exogeneously applied gibberellic acid causes considerable ultrastructural changes in aleurone cells (32,33). This discovery led to a large number of investigations concerning the mode of action of gibberellic acid on isolated aleurone layers, and the capability of aleurone cells to produce enzymes necessary for the degradation of the endosperm in the seed is now well established (5,15,17,19,20,21,23,39,40). Other studies have, however, shown that also the scutellum secretes enzymes (2,3,4,6,11,12,24,31).…”
Section: Introductionmentioning
confidence: 99%
“…Vigil and Ruddat (1973) found a 63 % inhibition of the discharge of a-amylase from barley aleurone by actinomycin D while there was only a 45 % inhibition of its synthesis. Furthermore, they found during the germination of these seeds, that there was an extremely active rER with numerous associated polysomes.…”
Section: Discussion (1) General Aspects Of the Discharge Of Secretionmentioning
confidence: 94%
“…Chrispeels (1972) found that neither affects the release of a-amylase by isolated barley aleufone cells or the incorporation of hydroxyproline-rich cell wall glyco-proteins into the wall of phloem-parenchyma cells in carrot root disc culture. The release of a-amylase in barley aleurone tissue apparently involves the fusion of endoplasmic reticulum (ER)-derived vesicles with the plasmalemma and is inhibited by inhibitors of protein synthesis (Vigil and Ruddat, 1973). The effect of these drugs on Dionaea is investigated here.…”
Section: Introductionmentioning
confidence: 99%